Overview of erythrocyte sedimentation rate examination results of farmers aged 30-40 years in Manunggal Karya Village Sub-district of Randangan District of Pohuwato - Abas, Niken Apriyani; Rita Amini Warastuti; Titin Dunggio (Journal of Health, Technology and Science (JHTS), 2023)
Pregnancy causes physical and emotional changes from pregnant women as well as social changes in the family. Pregnancy in general will continue to develop until a healthy baby is born through the birth canal. However, under certain conditions, sometimes the baby cannot be expelled through the birth canal. In this condition, a caesarean section is an alternative to remove the baby from the mother's stomach because normal delivery does not work and the baby does not come out after 20 hours than it should be. This can be caused by the size of the baby being too large against the birth canal, slowing of the cervical effacement or because the babies to be born are twins who are feared to slow down the birth process. This study aims to describe the results of the prothrombin time (PT) and activated partial thromboplastin time (APTT) examinations in pregnant women before surgery at the Bumi Panua Pohuwato Regional General Hospital, sub-district of Marisa, district of Pohuwato, province of Gorontalo. This research method used descriptive analysis with a quantitative approach. Sampling used an accidental sampling technique. The results showed that on the prothrombin time examination, 5 patients (16.7%) had abnormal PT results, while 25 patients (83.3%) had normal PT results. In the activated partial thromboplastin time examination using the same samples, 12 patients (40%) had abnormal APTT results and 18 patients (60%) had normal APTT results. The total sample was 30 pregnant women (100%).